Genetic variability, character association and path analysis in Brassica rapa L. Genotypes (Bangladesh Journal of Agricultural Research, 2015)
Thirty three genotypes of Brassica rapa L. were evaluated in order to find out their inter-genotypic variability; character association and path coefficient of seed yield/plant and its component characters. BARI sarisha-6 x TORI-7 S-45 showed best result in terms of early maturity (75 days) and higher seed yield/plant (5.28g) than check varieties. The character, plant height, was highly influenced by the environment whereas, all other characters influenced the least. Number of secondary branches/plant showed the highest phenotypic and genotypic coefficient of variation. Moreover, number of siliquae/plant, number of secondary branches/plant and number of primary branches/plant showed high heritability (93.16%, 75.69% and 68.03%, respectively) couple with high genetic advance in percent of mean (37.74%, 73.55% and 26.82%, successively). The seed yield/plant showed significant positive correlation with number of siliquae/plant (rg = 0.7011**, rp = 0.5684**), number of primary branches/plant (rg = 0.5611**, rp = 0.4016*) and number of secondary branches/plant (rg = 0.5160**, rp = 0.4098*) revealing that selection based on these traits would be judicious. Path analysis showed that the number of siliquae/plant (0.4679), number of primary branches/plant (0.2823) and number of secondary branches/plant (0.0092) were the most important contributors to seed yield/plant. The results indicated that number of siliquae/plant, number of primary branches/plant and number of secondary branches/plant can be used as selection criteria to increase seed yield/plant in rapeseed.Bangladesh J. Agril. Res. 40(2): 305-323 June 2015